Leveraging Mindsets to Promote Academic Achievement: Policy Recommendations. (November 2015) - Rattan, Aneeta; Savani, Krishna; Chugh, Dolly; Dweck, Carol S.
The United States must improve its students' educational achievement. Race, gender, and social class gaps persist, and, overall, U.S. students rank poorly among peers globally. Scientific research shows that students' psychology—their "academic mindsets"—have a critical role in educational achievement. Yet policymakers have not taken full advantage of cost-effective and well-validated mindset interventions. In this article, we present two key academic mindsets. The first, a growth mindset, refers to the belief that intelligence can be developed over time. The second, a belonging mindset, refers to the belief that people like you belong in your school or in a given academic field. Extensive research shows that fostering these mindsets can improve students' motivation; raise grades; and reduce racial, gender, and social class gaps. Of course, mindsets are not a panacea, but with proper implementation they can be an excellent point of entry. We show how policy at all levels (federal, state, and local) can leverage mindsets to lift the nation's educational outcomes.